1998
DOI: 10.1104/pp.117.4.1393
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of an Arabidopsis Gene Encoding Hydroperoxide Lyase, a Cytochrome P-450 That Is Wound Inducible1

Abstract: Hydroperoxide lyase (HPL) cleaves lipid hydroperoxides to produce volatile flavor molecules and also potential signal molecules. We have characterized a gene from Arabidopsis that is homologous to a recently cloned HPL from green pepper (Capsicum annuum). The deduced protein sequence indicates that this gene encodes a cytochrome P-450 with a structure similar to that of allene oxide synthase. The gene was cloned into an expression vector and expressed in Escherichia coli to demonstrate HPL activity. Significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
95
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 32 publications
(44 reference statements)
5
95
0
Order By: Relevance
“…4). In agreement with this conclusion, previous studies in which HPOD was incubated alone (Grosch, 1987) or in Escherichia coli extracts (Bate et al, 1998b) have also indicated that this compound readily autooxidizes to form hexanal.…”
Section: Cyp74b2 Enzyme Activities and C 6 Volatile Production In Difsupporting
confidence: 82%
See 4 more Smart Citations
“…4). In agreement with this conclusion, previous studies in which HPOD was incubated alone (Grosch, 1987) or in Escherichia coli extracts (Bate et al, 1998b) have also indicated that this compound readily autooxidizes to form hexanal.…”
Section: Cyp74b2 Enzyme Activities and C 6 Volatile Production In Difsupporting
confidence: 82%
“…Database analyses have indicated that there are six full-length CYP74B2 cDNA records having GenBank accession numbers AF087932 (Bate et al, 1998b), NM_117633 (reference sequence derived from an annotated genomic sequence NC_003075), BX827042, BX826974, BX826954, and BX826430; because the last four records are individual clones from a single cDNA library, they are considered as one source. Although records from all three sources report that they are derived from the Col ecotype, the last two sets of sequences (NM_117633 and four BX82XXXX) differ in the deletion of 10 nucleotides (nts; gray box in Fig.…”
Section: Sequence Polymorphism Of Cyp74b2 In Col and Ler Ecotypesmentioning
confidence: 99%
See 3 more Smart Citations